SPECIFIC ASPECTS OF PROVIDING HAVOC ON WEB-ORIENTED PLATFORMS - Zoxidov Jahongir Botirxonovich (American Journals, 2023)
The article reflects on the well-thought-out and secure architecture of Web-oriented platforms, in what way the standards of its basic technologies meet the requirements of compliance. The availability of software that implements the main capabilities of the .NET platform is highlighted - it allows you to choose this platform as a subject for training students of higher education institutions in the field of software development and use.
Keywords: Security, net platform, NTLM, authentication, authorization, IPS, RADIUS, DCOM, RPC.